Cold electron heating by EMIC waves in the plasmaspheric plume with observations of the Cluster satellite. Issue 6 (18th March 2014) - Yuan, Zhigang; Xiong, Ying; Huang, Shiyong; Deng, Xiaohua; Pang, Ye; Zhou, Meng; Dandouras, Iannis; Trotignon, Jean Gabriel; Fazakerley, Andrew N.; Lucek, Elizabeth
Abstract We report in situ observations by the Cluster spacecraft of plasmaspheric electron heating in the plasmaspheric plume. Electron heating events were accompanied by enhancements of electromagnetic ion cyclotron (EMIC) waves in the increased density ducts on the negative density gradient side for two substructures of the plasmaspheric plume. Electron heating is much stronger for the pitch angle of 0° and 180° than for the pitch angle of 90°. Theoretical calculations of the Landau resonant interaction between electrons and observed EMIC waves demonstrate that Landau damping of oblique EMIC waves is a reasonable candidate to heat cold electrons in the presence of O+ ions in the outer boundary of the plasmaspheric plume. Therefore, this observation is considered in situ evidence of plasmaspheric electron heating through Landau damping of EMIC waves in plasmaspheric plumes.